The Development of Academic Administration of Champasak Buddhist College, Lao People’s Democratic Republic - Chanthalath, Phra Khamsay; Panyapa, Assoc. Prof. Dr. Rattana; Khejornsa, Asst. Prof. (Special) Ruangdet (Journal for Developing the Social and Community, 2019)
The purpose of this research is to study the condition of academic administration, compare opinions of administrators and teachers about it, and study problems and guidelines for the development of academic administration according to the opinions of administrators and teachers at Champasak Buddhist College. The population and sample were 53 administrators and teachers. The questionnaire was used as a tool for data collection. The data is analyzed by frequency, mean, standard deviation. The differences were tested by using t-test and F-test (Scheffe method) was tested for pairing differences. The results showed that 1) The overall academic administration conditions were at a high level, 2) The comparison of opinions regarding the condition of academic administration in general were different at statistical significance of.05, 3) Problems and guidelines for academic administration development were found as follows: (1) Curriculum and Program Implementation: Some content, especially Buddhism, is very difficult, curriculum development plans should be adjusted appropriately to novices and monks as learners and teachers; (2) Teaching and learning management: study time is insufficient because there is only 4 hours of study per day, some subjects are not suitable for novices and monks, the study time should be increased and the subjects should be adjusted as suitable for the learners; (3) Teaching and learning media: textbooks, teaching materials and teaching media are not enough and modern, they should be provided; (4) Measurement and Evaluation: There is no follow-up evaluation, learners should be evaluated in many dimensions, and the experts should be invited to check the measuring tools.; (5) Internal supervision: There is little internal supervision, there is no field trips, teacher development programs and academic conferences should be organized every year.